RESULTS OF OZONE OBSERVATION FROM THE EQUATORIAL REGION TO ANTARCTICA IN 1987 - マツバラ, コウジ; ドイ, モトヒサ; ウエクボ, テツロウ; オカダ, ケンジ; アオキ, シュンジ; カワグチ, サダオ; MATSUBARA, Kouji; DOI, Motohisa; UEKUBO, Tetsuro; OKADA, Kenji; AOKI, Shuhji; KAWAGUCHI, Sadao (National Institute of Polar Research, 1991)
P(論文) The first total ozone observation and vertical ozone sounding on board the research vessel 'SHIRASE' from the equatorial region to Antarctica was carried out in 1987 by meteorological members of the 29th JARE (Japanese Antarctic Research Expedition) team. Total ozone and vertical ozone profile were measured by Brewer ozone spectrophotometer and ozonesondes, respectively. The detailed latitudinal distribution of total ozone amount and height-latitude distributions of ozone concentration, temperature and wind at 5-degree latitude intervals from the equatorial region to the Antarctic region were observed. From the ozonesonde observations, the injection of ozone from the stratosphere to the troposphere through the tropopause gap was deduced. The decreased ozone concentration in the lower stratosphere, similar to as same as the Antarctic ozone hole, was observed south of 60°S. It is possible that this phenomenon was caused by transport of ozone-poor air (a 'dilution effect') following the spring time ozone hole. departmental bulletin paper